Konsep Ekonomi Sirkular Model Circular Bisnis Circular dan Ekonomi Karbon Sirkular - Bonaraja Purba; Novita Sari Br Kaban; Rahel P.L Hutahaean; Teofilus Rahmat Zandroto; Imam Nur Dirham (Masyarakat Ekonomi Syariah Bogor, 2024)
This research discusses the implementation of a circular economy as a solution to reduce waste and carbon emissions. A circular economy focuses on sustainability by minimizing waste and maximizing resource use. This research uses qualitative research methods involving interviews, observation and document analysis. The research results show that implementing a circular economy can help reduce carbon emissions and increase awareness of the importance of protecting the environment. In carrying out community service, students are introduced to personal activities that support a circular economy. These activities involve presentation of material, discussions and questions and answers, as well as giving door prizes. Outcome result of this research show that implementing a circular economy can help increase students' awareness and behavior in protecting the environment.